A diversidade de portfólio de alianças e o desempenho das firmas industriais brasileiras em inovação de produto : o papel da capacidade de p&d e dos ativos complementares especializados - Moreira, Frederico Guilherme Pamplona (Universidade Federal de São Carlos, 2016)
The objective of this thesis was to analyze (1) the relationship between alliances portfolio diversity (DPA) and firm’s innovative performance and (2) whether firm’s R&D capacity (CAPPD) and specialized complementary assets (ACE) moderates this relationship. Finally, (3) whether CAPPD and ACE variables are complementary or substitute to each other. Thus, it was adopted an econometric method with secondary data. From Brazilian industry, were extracted 13,020 observations/companies from the last two databases PINTEC/IBGE - 2006-2008 and 2009-2011. The results confirmed an inverted U-shaped relationship between DPA and performance. Also confirmed that both moderating variables - CAPPD and ACE - positively moderates this curvilinear relationship. The substitute relationship between CAPPD and ACE was an unexpected result. The result of substitutability can be explained by inertial pressures imposed by firm's business model. These findings contribute to open innovation, in that emphasizes the relative importance of variety and not quantity of partners. The absorptive capacity theory (AC) is extended from the point which is seen as an element that has more than one dimension, not only in terms of skills and competencies, but also in spatial terms. The point of view of this thesis, the AC can manifest itself in areas other than firm’s R&D unit. Thus, the AC, while manifest itself in other internal sub-units can be indirectly connected to the firm’s knowledge and learning based view.
Keywords: Engenharia de produção; Inovação aberta; Diversidade de portifólio de alianças; Capacidade de p&d; Ativos complementares especializados; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO